Cultural Identity Sensibility and Belongingness Inadequacy in Jhumpa Lahiri’s Interpreter of Maladies: A Critical Analysis - Rahman, Muhd. Mustafizur (Integrated Journal for Research in Arts and Humanities, 2023)
Humans have had a special need and desire for the sense of ‘Identity’ ever since the first days of civilization. ‘Identity’ is the end result of everyone's efforts. A person has no value if he can't prove who he is. Human beings employ a variety of means (name, address, celebrity, fortune, popularity, etc.) to establish their position in the world. Many of the themes in Jhumpa Lahiri's books revolve on the tensions that arise between Indian and American cultures due to the author's background as a Bengali Indian American. Her protagonists are often members of the Indian diaspora who are homesick and lonely because to an identity conflict or a longing for the past and suffer from cultural identity sensibility and belongingness inadequacy. Her writings show how migrants feel about their adopted country, how they miss their homeland, and how they fight for a new place for themselves and suffer from cultural identity sensibility and belongingness inadequacy there, although they try to build a better economic and social life. Despite coming from a variety of backgrounds, all of Lahiri’s protagonists are stuck between two cultures: the one they left behind and the one to which they are trying to adapt and finally suffer from cultural identity sensibility and belongingness inadequacy. This clash of cultures is a recurring theme in her writing. Even while immigrants to the United States quickly adjust to daily life in the new country, they never lose their longing for the customs and culture of their birthplace. Although they benefit from a better environment and more opportunities, they are nonetheless influenced by their Indian heritage and hence have mixed feelings about life in the United States. This study examines how Jhumpa Lahiri’s Interpreter of Maladies deals with issues of cultural identity sensibility and belongingness inadequacy.